(untitled) (Research, Society and Development, 2022)
This study aims to identify the clinical and sociodemographic characteristics of Spotted Fever in Brazil between 2008 and 2017. A descriptive, retrospective, cross-sectional study with a quantitative approach that used as a source of data the Sistema de Informação de Agravos de Notificação (SINAN) available in the public database of the Departamento de Informática do Sistema Único de Saúde (DATASUS), adopting the following variables within the pre-established period: Region of Notification, Sex, Age Group, Evolution, Infection Zone, Schooling, Environment of Infection, and Confirmation Criteria. Spotted fever was prevalent in the Southeast region of the country, although underreporting is a reality in other regions. The most affected population was male, economically active, living in rural areas, and with incomplete primary education. Thus, epidemiological surveillance is fundamental, especially in endemic and "silent" regions for the notification of the disease.